Functional Assay to Correlate Protein Oligomerization States with Membrane Pore Formation - Šachl, Radek; Čujová, Sabína; Singh, Vandana; Riegerová, Petra; Kapusta, Peter; Müller, Hans-Michael; Steringer, Julia P; Hof, Martin; Nickel, Walter (Analytical chemistry, 2020)
In-membrane oligomerization is decisive for the function (or dysfunction) of many proteins. Techniques were developed to characterize membrane-inserted oligomers and the hereby obtained oligomerization states were intuitively related to the function of these proteins. However, in many cases, it is unclear whether the obtained oligomerization states are functionally relevant or are merely the consequence of nonspecific aggregation. Using fibroblast growth factor 2 (FGF2) as a model system, we addressed this methodological challenge. FGF2 oligomerizes in a PI(4,5)P2-dependent manner at the inner plasma membrane leaflet. This process results in membrane insertion and the formation of a lipidic membrane pore, the key intermediate in unconventional secretion of FGF2. To tackle the problem of discriminating functional oligomers from irrelevant aggregates, we present a statistical single molecule and single vesicle assay determining the brightness of individually diffusing in-membrane oligomers and correlating their oligomerization state with membrane pore formation. Importantly, time-dependent membrane pore formation was analyzed with an ensemble of single vesicles providing detailed statistics. Our findings demonstrate that quantifying oligomeric states alone does not allow for a deep understanding of the structure-function relationship of membrane-inserted oligomers.
Keywords: Protein Multimerization; poréznost; fibroblastový růstový faktor 2; Cell Membrane; permeabilita; kvarterní struktura proteinů; multimerizace proteinu; Protein Structure, Quaternary; Spectrometry, Fluorescence; unilamelární lipozómy; fluorescenční spektrometrie; Permeability; Unilamellar Liposomes; Fibroblast Growth Factor 2; buněčná membrána; Porosity